Diagnóstico da comercialização do pescado nas feiras de Manaus nos períodos de defeso e não defeso - Feio, Thalita Amorim (Instituto Nacional de Pesquisas da Amazônia - INPA, 2015)
The state of Amazonas is the largest producer of freshwater fish from Brazil, and most of the production is landed in Manaus. The consumption of this natural resource is a great expression of local culture, and most fish landed in Manaus are sold by brokers and retailers from the city. This paper aims to present fish trade characteristics in Manaus markets during in closed and open seasons, based on interviews with agents, merchants and consumers. Based on interviews and study of species for sale in Manaus markets, it is clear that arowana (Osteoglossum bicirrhosum), pacu (Mylossoma spp.), Sardines (Triportheus spp.), and tambaqui (Colossoma macropomum) were being sold in markets in the city during the closed season. There was no significant difference in the diversity of species marketed in closed and open seasons (P> 0.05). Studies of consumption patterns found that 77% of consumers eat fish once or twice a week, 17% ate fish three to four times a week and the other 6% reported consuming fish one to twice a month. Price was the most important factor for 77% of consumers when buying fish, while 20% considered quality the decisive factor and 3% gave the desired species as being most important. For male consumers, 59% said they did not have any food restriction, while 41% reported that they have restrictions when they have some kind of illness. For female respondents, 94% said they have a temporary food restriction, and will not eat certain species of fish when they are sick or when using a particular medication. The remaining 6% said they do not have any restriction. Overall, 86% of consumers reported ignoring the closed season and 14% of consumers said they know of the existence of the closed season, however, feel they do not have much information on the subject.
Keywords: Pesca; Comercialização do pescado